First trimester prenatal diagnosis of congenital rubella: a laboratory investigation. Issue 6525 (5th April 1986) - Terry, G M; Ho-Terry, L; Warren, R C; Rodeck, C H; Cohen, A; Rees, K R
Abstract : Acute primary maternal infection with rubella virus during pregnancy often, but not invariably, leads to the congenital rubella syndrome. Diagnosis by detection of virus specific IgM in the mother is not always possible, and in those cases in which IgM is detected the fetus has not necessarily also been infected. A method for direct, prenatal detection of fetal infection would allow more accurate early diagnosis of congenital rubella syndrome. In this study a case of suspected preconception rubella infection that was not referred until 14 weeks after the appearance of a rash was studied to determine whether a retrospective serological diagnosis of primary rubella could be made, and whether direct evidence of fetal infection could be obtained from a chorionic villus biopsy specimen by detecting virus specific antigens or ribonucleic acid (RNA) sequences. Monoclonal antibodies and a cloned complementary deoxyribonucleic acid probe were used successfully to detect antigens to rubella virus antigens and RNA sequences in the chorionic villus biopsy specimen, which was taken at 15 weeks' gestation. This method should serve as a new approach to the diagnosis of congenital rubella syndrome in utero.